Evaluation of Cecropin in circulating strains of Acinetobacter baumannii in the state of Rio de Janeiro - Freitas, Mariana Silva de (2025)
O item foi submetido ao 9th International Symposium on Immunobiologicals 2025 do Instituto de Tecnologia em Imunobiológicos.